2004
DOI: 10.2193/0022-541x(2004)068[0850:gvorcb]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variability of Reintroduced California Bighorn Sheep in Oregon

Abstract: Of the approximately 2,500 California bighorn sheep (Ovis canadensis californiana) in Oregon, USA, the majority descend from a single transplant of 20 animals from British Columbia, Canada, in 1954. Recently, several populations have experienced poor recruitment, raising concerns that populations may be experiencing inbreeding depression resulting from a genetic bottleneck. We sampled 117 animals from 5 populations in Oregon and 1 population in Nevada to determine genetic variability within and among populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
46
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(56 citation statements)
references
References 22 publications
6
46
3
Order By: Relevance
“…This occurrence was consistent with our previous report for the Indonesian native chickens (Riztyan et al, 2011). In commercial lines, the observed heterozygosity were slightly greater, which was in agreement with the result obtained by Whittaker et al (2004) and Lawson et al (2007) for the commercial sheep and domestic sheep, and Zanetti et al (2010) for the commercial chicken (brown layer) population and Italian breeds of chickens, where heterozygosity were greater than their wild relatives. They suggested that selective breeding are generally successful in maintaining diversity.…”
Section: Discussionsupporting
confidence: 93%
“…This occurrence was consistent with our previous report for the Indonesian native chickens (Riztyan et al, 2011). In commercial lines, the observed heterozygosity were slightly greater, which was in agreement with the result obtained by Whittaker et al (2004) and Lawson et al (2007) for the commercial sheep and domestic sheep, and Zanetti et al (2010) for the commercial chicken (brown layer) population and Italian breeds of chickens, where heterozygosity were greater than their wild relatives. They suggested that selective breeding are generally successful in maintaining diversity.…”
Section: Discussionsupporting
confidence: 93%
“…Despite significant heterozygote deficit, levels of heterozygosity are relatively high in commercially managed breeds compared to the primitive, feral or wild sheep such as the Californian bighorn sheep, where H o ¼ 0.28-0.36 (Whittaker et al, 2004). A similar situation is found in domestic goats, which have substantially higher heterozygosity than their wild relatives (Saitbekova et al, 1999).…”
Section: Discussionmentioning
confidence: 95%
“…Many of these loci have been examined in previous publications [6,9,10], and we have used them to examine heterozygosity in different populations of bighorn sheep across their range in North America (unpublished). Briefly, using fluorescently labeled microsatellite primers, microsatellites present in genomic DNA were amplified by PCR (polymerase chain reaction).…”
Section: Methodsmentioning
confidence: 99%